Spatiotemporal Patterns of Human–Carnivore Encounters in a Seasonally Changing Landscape: A Case Study of the Fishing Cat in Hakaluki Haor, Bangladesh - Afsana Nasreen Eva; Ai Suzuki; Shinya Numata (Conservation, 2022)
Identifying spatial and temporal patterns of human–carnivore encounters is crucial for predicting conflict hotspots. However, the degree of overlap between human and carnivore movements is likely to differ between stable environments and seasonally changing landscapes. We aimed to clarify key drivers of spatial and temporal overlap of humans and carnivores in a seasonally changing landscape using the case of human–fishing cat encounters in an inland wetland in north-eastern Bangladesh. To obtain encounter information, interview surveys were conducted with 210 respondents in 21 villages in 2020. Monthly rainfall and waterbody size were negatively correlated with the numbers of encounters in the wetland area, while there was no apparent temporal pattern in encounters reported in adjacent villages. Temporal patterns of encounters may be partially explained by human presence (in turn associated with local livelihoods). Except for fishing, intense livelihood activities take place in wetland areas mainly during the dry season. On the other hand, areas peripheral to the wetlands are used for various livelihood activities throughout the year. In a seasonally changing landscape, understanding people’s movements could help elucidate spatiotemporal patterns of human–fishing cat encounters at a micro-scale.